INCIDENTAL FINDING OF SOLITARY FIBROUS TUMOR OF MALE BREAST - El-Helou, Etienne; Zaiter, Manar; Delrue, Pauline; Awada, Ahmad; Veys, Isabelle; Pop, Catalin-Florin (Mastology, 2026)
Myofibroblastoma (MFB), also known as a solitary fibrous tumor of the breast, is a rare sporadic benign tumor composed of spindle-shaped tumor cells with myoblast differentiation. The most typical presentation is a painless unilateral mass that is not connected to any surrounding structure and seldom surpasses 3 cm in size and should be evaluated by using the triple-assessment approach. They have several subtypes, and a definite diagnosis can only be confirmed safely after surgery using immunohistochemistry. Surgical excision serves an essential diagnostic and therapeutic purpose; MFB has a favorable prognosis even when excision margins are positive, and local recurrence is extremely rare. The following is the case of a 73-year-old man who presented with a dry cough. An MFB was discovered by chance during the investigative workup and referred to our department. The patient’s presentation, imaging, and histological samples all supported the diagnosis, and he had surgical resection without incident. We present the second case of an incidental finding of breast MFB and urge clinicians to consider this differential diagnosis.